God"s mercy revealed in the ministry of charity: The Church in Poland reaching out to "the periphery" - Przygoda, Wiesław A. (HTS teologiese studies, 2020)
The ministry of charity is an important dimension of the Church’s mission, because in this way it shows the mercy of its founder to the world. Christians incarnate God’s mercy to the world by serving other people. This is how we should understand the words of Pope Francis, who said that the Church needs to reach out to the periphery, i.e. the poor, the homeless, the migrants, the unemployed, the sick and the socially excluded. What the essence of God’s mercy is how it is shown in the community of the Church and how the Church in Poland takes care of those who remain on the periphery of the world. These are the questions which the author of this article will try to answer. The reflection undertaken is mainly based on biblical sources and the teaching of Pope Francis.Contribution: Theological reflection on God’s mercy, combined with a reflection on the ways of concrete help for socially excluded people, based on the example of the Church’s charitable initiatives in Poland, is a contribution to the development of existential and inclusive ecclesiology, which is postulated by Pope Francis. It also shows how research in the field of practical theology can use the achievements of contemporary praxeology. This juxtaposition of theological and praxeological fields of reflection coincides with the focus and scope of the journal to promote the multidisciplinary aspects of studies in the general theological area.